Ibn Hisham Al-Ansar's notes on Al-Tibyan fi I’rab Al-Quran by Al-Akbari in light of the points of objection to the grammarians in Mughni Al-Labib (what was contrary to the original) - Mohammed, Lobna; Jasem , Yesraa (Al-Adab Journal, 2025)
The book "Mughni al-Labib about”al-A'arib" books by Ibn Hisham al-Ansari is considered one of the most prominent works in Arabic grammar, as it deals with various grammatical issues, and devotes a part of it to responding to the opinions of some previous grammarians. Among these responses, the "Ten Sides" “ Al Jehatt Al Ashraa “that Ibn Hisham used as a methodology in discussing and correcting some grammatical concepts stand out. In it, he showed the errors that grammarians make in grammar. Ibn Hisham’s responses to grammarians were not limited to his book, Mughni al-Labib, but rather included most of his works, including his book, Ibn Hisham’s Commentaries on al-Akbari’s al-Tibyan. The purpose of my study is to direct Ibn Hisham’s responses in this book according to the ten aspects that he mentioned in Mughni al-Labib. In this section, we will mention the issues in which Ibn Hisham differed with al-Akbari according to one of the aspects that he referred to, which are: (that it is issued contrary to the original, or contrary to the apparent meaning for no reason), in which Ibn Hisham showed the scholars’ errors in estimating the omitted.